Effect of Quercetin on Lipids Metabolism Through Modulating the Gut Microbial and AMPK/PPAR Signaling Pathway in Broilers - Wang, Mi; Wang, Bo; Wang, Shanshan; Lu, Han; Wu, Hao; Ding, Manyi; Ying, Linlin; Mao, Yanjun; Li, Yao (Frontiers in Cell and Developmental Biology, 2021)
The present study was conducted to investigate effects and mechanism of quercetin on lipids metabolism in broilers. 480 AA broilers were randomly allotted to four treatments (0, 0.2, 0.4, and 0.6 g /kg quercetin) for 42 days. Compared with the control, 0.6 g/kg quercetin significantly decreased percentage of abdominal fat (P<0.05); 0.2, 0.4 and 0.6 g/kg quercetin significantly decreased relative abundance of Lachnospiraceae and Desulfovibrionaceae (P<0.05, P<0.05, P<0.01; P<0.01, P<0.01, P<0.01); 0.2 g/kg quercetin significantly increased mRNA expression of PI3K, AMPKα1, AMPKα2, AMPKβ2, LKB1 (P<0.01, P<0.01, P<0.05, P<0.01, P<0.05), and significantly reduced mRNA expression of SREBP1 and PPARγ (P<0.01, P<0.05 ); 0.4 g/kg quercetin significantly increased mRNA expression of LKB1 and PKB (P<0.05, P<0.01) and significantly reduced mRNA expression of ACC, HMGR, PPARγ and SREBP1 (P<0.05, P<0.01, P<0.01, P<0.01); 0.6 g/kg quercetin significantly increased mRNA expression of AMPKγ, LKB1, CPT1, PPARα, PKB (P<0.01, P<0.01, P<0.01, P<0.05, P<0.05), and significantly reduced the mRNA expression of PI3K, ACC, HMGR, PPARγ, SREBP1 (P<0.05, P<0.05, P<0.01, P<0.01, P<0.01); 0.2 g/kg quercetin significantly increased protein expression of AMPK (P<0.01); 0.6 g/kg quercetin significantly increased protein expression of LKB1 (P<0.01), 0.2 and 0.6 g/kg quercetin significantly increased protein expression of PI3K, PKB, CPT1 (P<0.05, P<0.01, P<0.05, P<0.01, P<0.01, P<0.01 ), and significantly reduced protein expression of ACC and SREBP1 (P<0.01, P<0.01, P<0.01, P<0.01). In conclusion, quercetin improved carcass characteristics and chicken quality by gut microbial metabolism and AMPK/PPAR signaling pathway in broilers.